AXIOM, HYPOTHESIS, AND THEORY AS FUNDAMENTAL CONCEPTS OF SCIENTIFIC METHODOLOGY (American Journal of Technology and Applied Sciences, 2025)
This article explores the fundamental concepts of axiom, hypothesis, and theory in the methodology of science. It analyzes their interconnections, differences, and roles in scientific research. The study is based on a comparative analysis of these terms, supported by historical examples from mathematics, physics, and economics. The paper also examines the process of transitioning from a hypothesis to a theory and the conditions under which theories may evolve into axioms. The discussion highlights the role of scientific paradigms, as described by Kuhn and Popper, in shaping scientific knowledge. The findings emphasize the dynamic nature of scientific theories and their dependence on empirical validation.